2020
DOI: 10.1186/s41073-020-00093-0
|View full text |Cite
|
Sign up to set email alerts
|

Grant reviewer perceptions of the quality, effectiveness, and influence of panel discussion

Abstract: Background: Funding agencies have long used panel discussion in the peer review of research grant proposals as a way to utilize a set of expertise and perspectives in making funding decisions. Little research has examined the quality of panel discussions and how effectively they are facilitated. Methods: Here, we present a mixed-method analysis of data from a survey of reviewers focused on their perceptions of the quality, effectiveness, and influence of panel discussion from their last peer review experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Our results are limited by a relatively low response rate, although this response rate approximates the rate of similar surveys on peer review (Gallo et al 2020a;Ware 2008). The majority of funding agency comments in our survey mentioned the NIH as a recent source of review feedback; the gender, race, and degrees of our sample are similar to those reported from surveys and analyses of NIH applicants (NIH 2012a;Ginther et al 2011Ginther et al , 2016.…”
Section: Generalizabilitymentioning
confidence: 55%
See 1 more Smart Citation
“…Our results are limited by a relatively low response rate, although this response rate approximates the rate of similar surveys on peer review (Gallo et al 2020a;Ware 2008). The majority of funding agency comments in our survey mentioned the NIH as a recent source of review feedback; the gender, race, and degrees of our sample are similar to those reported from surveys and analyses of NIH applicants (NIH 2012a;Ginther et al 2011Ginther et al , 2016.…”
Section: Generalizabilitymentioning
confidence: 55%
“…Given the paucity of data surrounding grant review feedback, particularly from an applicant’s perspective, we created a survey for research scientists that asked applicant respondents to rate and comment on the review feedback they received on their most recent submission. Three publications have resulted from this survey (Gallo et al 2018 ; Gallo et al 2020a , b ), but none of them focused on the questions related to the usefulness and appropriateness of peer review feedback; these questions are now addressed in the proceeding analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show no significant difference in the quality of the decision making in teams using written (text-only) or audio-only communication (Gallo et al 2013), but do show a benefit of adding video formats (including videoconferencing facilities) resulting in a significant improvement in the quality of team's deliberations and resultant strategic decision making (Baker 2002). Comparative research on the scoring patterns of peer reviews of traditional academic criteria has found only subtle differences in those between F2F and virtual panels; however, there was a decrease in discussion quality when deliberations were conducted virtually (Carpenter et al 2015;Gallo, Carpenter, and Glisson 2013;Gallo et al 2020). This is the case regardless of whether virtual deliberation is conducted using video conferencing, instant messages or other supported web technologies (such as parallel chat functions) (Carpenter et al 2015;Gallo, Carpenter, and Glisson 2013;Gallo et al 2020;Pier et al 2017).…”
Section: Consideration 1: Maintaining Sufficient Peer Review Deliberation In the Virtual Settingmentioning
confidence: 99%
“…Comparative research on the scoring patterns of peer reviews of traditional academic criteria has found only subtle differences in those between F2F and virtual panels; however, there was a decrease in discussion quality when deliberations were conducted virtually (Carpenter et al 2015;Gallo, Carpenter, and Glisson 2013;Gallo et al 2020). This is the case regardless of whether virtual deliberation is conducted using video conferencing, instant messages or other supported web technologies (such as parallel chat functions) (Carpenter et al 2015;Gallo, Carpenter, and Glisson 2013;Gallo et al 2020;Pier et al 2017). Thus, regardless of the sophistication of web-technologies to attempt to recreate the benefits associated with F2F, F2F remains the preferred, and more efficient mechanism to support complex decision-making, with this effect amplified for new panel groups (O'Neill et al 2016).…”
Section: Consideration 1: Maintaining Sufficient Peer Review Deliberation In the Virtual Settingmentioning
confidence: 99%
“…Given the paucity of data surrounding grant review feedback, particularly from an applicant's perspective, we created a survey for research scientists that asked applicant respondents to rate and comment on the review feedback they received on their most recent submission. Three publications have resulted from this survey (Gallo et al 2018, Gallo et al 2020a, Gallo et al 2020b), but none of them focused on the questions related to the usefulness and appropriateness of peer review feedback; these questions are now addressed in the proceeding analysis.…”
Section: Introductionmentioning
confidence: 99%